O ensino remoto emergencial em tempos de pandemia: limites e possibilidades na graduação em enfermagem. - Girardello, Debora Tatiane Feiber (2022)
The Covid-19 pandemic, caused by the SARS-CoV-2 virus, surely imposed social, health, economic and educational changes that will be remembered and studied over time. Considering this context and the need to continue the process of school training, Emergency Remote Teaching (ERT) emerged as the most appropriate possibility, from a health point of view, for the permanence of didactic-pedagogical work in schools of basic and higher education. However, this method of teaching has been discussed nowadays and criticisms have been made about the development of the ERE. When considering this issue, the general objective was to identify, from the perception of professors and students, the limitations, and possibilities of emergency remote teaching in undergraduate nursing throughout the Covid-19 pandemic. This is a case study, combining an integrative literature review, about the central theme, with a descriptive exploratory study and a qualitative approach. The integrative literature review aimed to understand how the development of higher education ERT has been approached in scientific literature in the health area in Brazil, which explored the databases of Latin American and Caribbean Literature in Health Sciences (Lilacs), in the Nursing Database (BDENF) and Medline via Pubmed, and in the Scientific Electronic Library Online (SciELO), using the descriptor: Emergency Remote Teaching and Ensino Remoto Emergencial in English and Portuguese for the searches that took place on June 5, 2021. The data analysis and systematization allowed us to identify, among the selected articles, two different themes related to the development of ERT in higher education in health, namely: the impact of Emergency Remote Teaching on academic training and didactic proposals/strategies for Emergency Remote Teaching. The exploratory study with a quantitative and qualitative approach, with data collected in July and August 2021, with 14 professors and 56 nursing students as participants from a higher education institution in Western Paraná, which offers the nursing course. Data collection was performed using Google Forms®, and the responses were systematized and analyzed using Content Analysis. The results were presented in two articles, which explained that Emergency Remote Teaching was a necessary and important choice that positively cooperated with permanent training, in addition to contributions that remains in the educational field, but exposes weaknesses that need reassessment, in a new need to use Emergency Remote Teaching. The study problematized Emergency Remote Teaching and its relationship with Distance Learning, as well as the elements that influenced the teaching-learning process at the time of the pandemic, showing that the interaction between teacher and student was impacted in the teaching-learning process.